2016
DOI: 10.1002/chem.201504984
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Diels–Alder Reaction of Graphene Oxide

Abstract: Graphene oxide is regarded as a major precursor for graphene-based materials. The development of graphene oxide based derivatives with new functionalities requires a thorough understanding of its chemical reactivity, especially for canonical synthetic methods such as the Diels-Alder cycloaddition. The Diels-Alder reaction has been successfully extended with graphene oxide as a source of diene by using maleic anhydride as a dienophile, thereby outlining the presence of the cis diene present in the graphene oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…Nevertheless, it represents a significant change with respect to pristine graphene since the reaction is possible thanks to the presence of these two oxygen atoms. These findings are in line with the results obtained by Brisebois et al., which indicated that the Diels‐Alder reactions are more likely to occur onto graphene oxide as compared with pristine graphene. In effect, the functional groups present in graphene oxide increase the diene character of graphene.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, it represents a significant change with respect to pristine graphene since the reaction is possible thanks to the presence of these two oxygen atoms. These findings are in line with the results obtained by Brisebois et al., which indicated that the Diels‐Alder reactions are more likely to occur onto graphene oxide as compared with pristine graphene. In effect, the functional groups present in graphene oxide increase the diene character of graphene.…”
Section: Figuresupporting
confidence: 93%
“…decided to investigate whether graphene can behave as diene or dienophile. This landmark investigation created a new subfield in the covalent functionalization of graphene, and several experimental and theoretical works have been performed to shed light into the thermodynamical and kinetics aspects of the [4+2] cycloadditions on 1D and 2D based carbon nanomaterials . Higher order [6+4] cycloaddition reactions are possible as Houk and Woodward showed as early as 1970, even though it is well known that they are much more difficult to attain than [4+2] Diels‐Alder reactions .…”
Section: Figurementioning
confidence: 99%
“…Among them, we can highlight: the addition of aryl diazonium salts, alkylation, 1,3 dipolar cycloadditons, [2+2] cycloadditions, [2+1] cycloadditions . and the Diels‐Alder reactions, where graphene can be either diene or dienophile . As early as 2011, Sarkar et al .…”
Section: Introductionmentioning
confidence: 95%
“…High level theoretical calculations performed by us and Cao et al., showed that the central part of graphene, i. e. perfect graphene, is unreactive against TCNE, MA, 9MA and DMBD. Defects, edges, curvature, heating, force accelerated processes, or the presence of hydroxyl groups are required to achieve a successful Diels‐Alder reaction onto graphene. Bearing in mind that the diene/dienophile character of graphene depends on how the electron density is distributed over the CC bonds, we reasoned that it may be possible to facilitate Diels‐Alder reactions onto graphene by the introduction of the adequate heteroatoms onto graphene.…”
Section: Introductionmentioning
confidence: 99%
“…[105] Brisebois et al suggested that the reaction can occur through two different pathways: with a 1,3butadiene system (marked in red, Scheme 5a) or, through a cis-3,5-cyclohexadiene-1,2-diol system (marked in blue, Scheme 5b), in which both À OH groups are facing the opposite side of the MA addition to avoid steric hindrance. [106] GO may also act as a dienophile in addition to the previously discussed behavior as a diene. Tang et al have evaluated both the diene and dienophile character of GO in the presence of MA and of 2,3-dimethoxybutadiene (DMBD), respectively.…”
Section: Cycloaddition Reactionsmentioning
confidence: 89%